Ambiente en el aula, ambiente de aprendizaje y desempeño educativo en Bogotá (2017)
"In the school effectiveness discussion, this article highlights the importance of classroom environment (quality of student?s relationships) and learning environment (quality of relationships between teachers and students) as key factors that determinate educational performance in standardized tests. This paper explores the relationships between both components of school environment and educational attainment in primary and secondary schools in Bogotá with a focus on language and mathematics. Using multiple regressions throughout Ordinary Least Square (OLS) method of estimation, this article obtains two robust models, one for primary schools, and the other one for secondary schools which allow to identify the impact of both school environmentïs components on educational achievement. We found that in primary schools there wasnït a significant relationship between classroom environment and educational achievement. Nonetheless, we found that learning environment has an effect on language results. A ten per cent increase in that factor is associated with a 4.5% increase in language-standardized test." -- Tomado del Formato de Documento de Grado.